Anti-IL-20 Antibody Protects against Ischemia/Reperfusion-Impaired Myocardial Function through Modulation of Oxidative Injuries, Inflammation and Cardiac Remodeling - Kun-Ling Tsai; Wan-Ching Chou; Hui-Ching Cheng; Yu-Ting Huang; Ming-Shi Chang; Shih-Hung Chan (MDPI AG, 2021)
Acute myocardial infarction (AMI) is the most critical event in the disease spectrum of coronary artery disease. To rescue cardiomyocytes in AMI, it is important to restore blood supply as soon as possible to reduce ischemia-induced injury. However, worse damage can occur during the reperfusion phase, called the reperfusion injury. Under ischemia/reperfusion (I/R) injury, elevated oxidative stress plays a critical role in regulation of apoptosis, inflammation and remodeling of myocardium. Our previous study has demonstrated that interleukin (IL)-20 is increased during hypoxia/reoxygenation stimulation and promotes apoptosis in cardiomyocytes. This study was, therefore, designed to investigate whether IL-20 antibody could reduce I/R-induced myocardial dysfunction. Results from this study revealed that IL-20 antibody treatment significantly suppressed I/R-induced nicotinamide adenine dinucleotide phosphate oxidase, oxidative stress, apoptosis, proinflammatory responses, cardiac fibrosis, and expression of cardiac remodeling markers in Sprague-Dawley rats. Plasma B-type natriuretic peptide level was also reduced by IL-20 antibody injection. IL-20 antibody treatment appeared to restore cardiac function under the I/R injury in terms of greater values of ejection fraction and fractional shortening compared to the control group. Two commonly used indicators of cardiac injury, lactate dehydrogenase and creatine kinase-MB, were also lower in the IL-20 antibody injection group. Taken together, our results suggested that IL-20 antibody holds the potential to reduce the I/R-elicited cardiac dysfunction by preventing cardiac remodeling.